Muscle Dysmorphia Research Neglects DSM-5 Diagnostic Criteria. Issue 3 (3rd April 2018) - Sandgren, Sebastian S.; Lavallee, David
ABSTRACT: This systematic review aimed to collect, evaluate, and synthesize the research on muscle dysmorphia (MD) post official recognition as a specifier for body dysmorphic disorder (BDD) in the DSM-5, and provide recommendations for future research. Literature searches were conducted in four databases to see if inclusion criteria were met. Results revealed 33 studies meeting inclusion criteria, none of which utilized DSM-5 criteria for MD or acknowledged the criterion in their research. Few studies acknowledged the association between MD and BDD, and the methodological quality of recent MD research was considered low due to a lack of clinical samples, measurements not using validated cutoff scores, and the research designs. In conclusion, future MD research is encouraged to utilize DSM-5 diagnostic criteria to better inform clinical practice and significantly improve the methodological quality. As such, more effective treatment options may be developed, reducing the risk of health-harming consequences in these individuals.